Dual installations – legal conditions - Kępa, Urszula (Instal, 2025)
In the face of increasing water shortages in Poland and the frequent occurrence of hydrological droughts, it has become necessary to implement solutions that enable more sustainable water resource management. One such solution is dual installations, which allow the use of rainwater and/or treated greywater for household purposes, such as toilet flushing, irrigation, or laundry. The article discusses current legal regulations and technical standards related to such installations, highlighting significant gaps in national legislation and the need for updates. Proposed definitions for new concepts, such as “utility water” and “grey wastewater” vs. “greywater,” are presented. The requirements of standards for non-potable water installations (PN-EN 16941-1 and PN-EN 16941-2) are examined. Solutions that could enable broader practical application of these systems are suggested. Additionally, available systems on the Polish market, along with their benefits and limitations, are analyzed. Dual installations can play a key role in climate change adaptation and achieving sustainable development goals in water and wastewater management, but their widespread adoption requires legislative and financial support.
Keywords: dual installations; water reuse; greywater; rainwater; legal standards